2011
DOI: 10.1248/cpb.59.855
|View full text |Cite
|
Sign up to set email alerts
|

seco-Limonoids and Quinoline Alkaloids from Raputia heptaphylla and Their Antileishmanial Activity

Abstract: Regular ArticleThe Rutaceae family, consisting of ca. 150 genera and 1600 species, is mostly distributed throughout tropical regions. Species from this family have important uses in industry such as in food, pharmaceuticals and ornamental purposes, as well as having a wide variety of ethnobotanical uses 1) ; they are studied in terms of obtaining alkaloids and limonoids as bioactive principles.2) Among important plants from Rutaceae, those from the Raputia genus have attracted special attention because of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
3
21
0
3
Order By: Relevance
“…When developing in vitro screens to study bioactive molecules for the control of this microorganism, there is a necessity for developing assays to evaluate possible antiparasitic activities against parasites of the genus Leishmania at the different life cycle stages of this pathogen. It is particularly important to develop antiparasitic therapies against the form of the pathogen responsible for the disease in the vertebrate host during the clinical manifestations of the disease [34,35], and is in this way, that in the present study we confirmed the efficacy of a seco-limonoid (triterpene) [18] which exhibits activity against only the intracellular form of the parasite, leading to a decrease and subsequent resolution of the infection in treated infected cells. We demonstrated that this activity is related to an immunomodulatory mechanism of action in which the compound induces an apparent "reactivation" of the "paralyzed" APC caused by the survival mechanisms developed by the pathogen.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…When developing in vitro screens to study bioactive molecules for the control of this microorganism, there is a necessity for developing assays to evaluate possible antiparasitic activities against parasites of the genus Leishmania at the different life cycle stages of this pathogen. It is particularly important to develop antiparasitic therapies against the form of the pathogen responsible for the disease in the vertebrate host during the clinical manifestations of the disease [34,35], and is in this way, that in the present study we confirmed the efficacy of a seco-limonoid (triterpene) [18] which exhibits activity against only the intracellular form of the parasite, leading to a decrease and subsequent resolution of the infection in treated infected cells. We demonstrated that this activity is related to an immunomodulatory mechanism of action in which the compound induces an apparent "reactivation" of the "paralyzed" APC caused by the survival mechanisms developed by the pathogen.…”
Section: Discussionsupporting
confidence: 78%
“…of a seco-limonoid (11α,19β-dihydroxy-7-acetoxy-7-deoxoichangin), which was isolated from the bark of Raputia heptaphylla (Rutaceae family), which was previously described by Coy and colleagues [18]. We suggest here a possible mechanism for the antiparasitic activity of this compound that is related to the immunomodulatory effect on APCs.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Section 3). Ichangin (8) (from C. ichangensis) has also been recently isolated from the stem bark and leaves of the South-Americaan plant, Raputia heptaphylla [141]. It may be considered as the product of hydrolytic cleavage of the oxygen-containing portion of the isobenzofuran nucleus of 1 (A' ring).…”
Section: Deacetylnomilin (4)mentioning
confidence: 99%